Impact of Deviant Workplace Behavior in The Internal Organizational Crises: An Empirical Study - Mishrif, Abbas Muzel; Ghaly, Haider Hussain (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to explore the extent of Deviant workplace behavior in internal organizational crises, in the General Directorate of Education of Najaf. To achieve the objectives of the research, influence and correlation relationships between the dimensions of the variables were studied. Using the descriptive-analytical method, (99) questionnaires were distributed directly to the target community. (94) Forms were retrieved, and the number of valid questionnaires for statistical analysis was (90). After presenting the collected data and analyzing it by identifying the consistency of the sample responses on the questionnaire paragraphs and selecting hypotheses using the statistical programs represented by (SPSS.V.20, SMART PLS). The results show the validity of the research hypotheses. Therefore, a number of conclusions were reached and a set of recommendations was developed.